Em busca de Beatriz: análise semiótica de “Uma Carta” de Sérgio Sant’anna - Thomé, Vânia dos Reis Rodrigues (2009)
This work analysis , having as Theory the French semiotic line, the tail “Uma Carta”/A Letter from Sérgio Sant‟anna‟s book, O Monstro/The Monster, the aim is to go into the feminine universe of Beatriz who searches for the own living reason of her “Myself”. With this objective the research describes in which way the semioticists Greimas, Bertrand and Landowski articulate their theories. From the definition, to learn from the scientific French semiotic method, some specific relationship are gone over between the Linguistic of Hjemslev and the other semioticists, it is also said about the North American Semiotic to differentiate it from the French one, getting to the theory of French Hjelmlev Semiotic founding discourse and to other works which helped him in the development of his theory. In the Tail, the object of analysis is seen; the reflection of the enunciator on the act of the spelling of the work of art “Uma Carta” and on the building of the actor of enunciation and of the enunciator Beatriz is the characteristics shown over the tail. Considering, the check on how the text happens that clearly organizes the written discourse from the author‟s point of view (met discourse) and how the actor builds himself/herself in the seeking for his own “me”, makes the bases of the analysis of the tail, always supported by the Semioticists. The narrator, simulation of Beatriz subject, tells the dating with his lover Carlos. In this sense, the subject of the enunciator changes into the letter in which the enunciator is named Beatriz. Like this, Beatriz builds herself as an actor of a past dating with her lover, looking for reviewing those emotions of fear, danger, desire, frustration, among others, where each sentiment represents different thematic.